Serum anti‐Mullerian hormone levels across different ethnic groups: a cross‐sectional study. (7th October 2014) - Bhide, P; Gudi, A; Shah, A; Homburg, R
<x xml:space="preserve">Abstract</x> Objective To assess whether ethnic differences in serum anti‐Mullerian hormone (AMH) exist in a population of subfertile women presenting to a fertility clinic. Design Observational cross‐sectional study. Setting Homerton University Hospital Fertility Centre, London, UK. Population A total of 865 women attending the fertility clinic for their first consultation appointment between September 2012 and September 2013. Methods Serum AMH was compared amongst women from five different ethnic groups. Main outcome measures Serum AMH and ethnicity were the primary outcome variables. Results Although initial comparison showed South Asian women to have a higher serum AMH, compared with white European and Afro‐Caribbean women (F = 3.817; P < 0.005), South Asian women attending the clinic were significantly younger and less likely to be smokers than women from other ethnic groups. The prevalence of polycystic ovary syndrome (PCOS) was significantly higher in South Asian and South East Asian women than in other ethnic groups. Differences in serum AMH were no longer significant after controlling for confounding factors: age, body mass index (BMI), and smoking status with (P = 0.869) and without (P = 0.215) controlling for PCOS. Conclusion The results from our study show that there was no independent association of ethnicity and serum AMH levels in an unselected population of women attending the fertility clinic.